Interaction of Thrombin-Stimulated Platelets with Vitronectin (S-Protein of Complement) Substrate: Inhibition by a Monoclonal Antibody to Glycoprotein IIb-IIIa Complex - Thiagarajan, Perumal; Kelly, Kathleen (Thrombosis and Haemostasis, 1988)
Platelets adhere to vitronectin substrate following activation with physiological concentrations of thrombin. Adhesion of activated platelets to vitronectin substrate is dependent upon the presence of divalent cations, the amount of vitronectin, and the duration of adhesion assay. The adhesion of platelets is inhibited by synthetic peptides containing the sequence of Arg-Gly-Asp. In addition, monoclonal antibodies to glycoprotein IIb-IIIa complex inhibit the adhesion of activated platelets to vitronectin substrate in a dose-dependent manner. These studies suggest that the glycoprotein IIb-IIIa complex on activated platelets may interact with vitronectin substrate through the Arg-Gly-Asp mechanism. Since vitronectin is present in the subendothelial matrix, it might be involved in platelet-vessel wall interactions
Keywords: Platelet adhesion; Vitronectin; Glycoprotein IIb and IIIa